Support and trust in the government and COVID-19 experts during the pandemic - Yokoyama, Hiromi M.; Ikkatai, Yuko (Frontiers in Communication, 2022)
Support in government and trust in COVID-19 experts are important for pandemic preparedness. Based on the salient value similarity (SVS) model, which holds that “salient values” are important for trust in risk management, we measured ruling and opposition party supporters' support and trust in the government and COVID-19 experts. Comparing the results from 2020 and 2022, supporters of the ruling party maintained their support for the government, while supporters of the opposition party changed from disapproval to support. Trust in experts was higher among ruling party supporters and lower among opposition party supporters. Trust in university researchers did not differ between the ruling and opposition parties. This reveals that it is possible for a government to gain support from opposition party supporters and that achieving trust in experts who advise the government is more difficult than fostering trust in ordinary scientists.